The Influence of Quality Work of Life on Performance with Subjective Well-Being as a Mediator - Jainudin, Syarul; Wiyarni, Wiyarni; Mauludin, Hanif (PT. EQUATOR SINAR AKADEMIA, 2025)
A high-Quality Work of Life is believed to enhance employee performance, particularly when supported by strong psychological well-being. This study aims to examine the effect of Quality of Work Life on employee performance, with Subjective Well-Being as a mediating variable. A quantitative approach was employed using a survey method involving 100 permanent employees at the Class I Correctional Institution in Malang. Data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results show that Quality of Work Life has a significant effect on both Subjective Well-Being and employee performance. Furthermore, Subjective Well-Being plays a mediating role in this relationship. These findings imply that improving the quality of the work environment not only directly enhances performance but also does so indirectly through the improvement of employees' psychological well-being